Study on Crystallization and Magnetic Property Deviation of Ni-Zn-Cu Ferrite Depending on the State of the Starting Material in the Annealing Process - Su-won Yang; Kwang-pil Jeong; Jeong-gon Kim (Advances in Materials Science and Engineering)
The spinel structure of the nanosize powder (Ni0.3Zn0.3Cu0.4Fe2O4) substituted by Ni, Zn, and Cu was fabricated by the sol-gel process. Changes in weight, crystal formation, and magnetic properties were observed by XRD, TG-DTA, VSM in the annealing process of the sol and gel. The saturation magnetization of the sol showed 54.8–58.6 emu/g at 500–800°C, and the gel showed 52.3–56.8 emu/g at 600–800°C. The coercive force of the sol decreased in the range −136 Oe to −11.4 Oe at 500–800°C, and the gel decreased in the range −95 Oe to −44 Oe at 600–800°C. Therefore, the deviation of the annealing temperature of the nanopowder fabricated in the sol process and the gel process was about 100°C.